2022
DOI: 10.3390/su14031434
|View full text |Cite
|
Sign up to set email alerts
|

Energy Potential and Sustainability of Straw Resources in Three Regions of Ghana

Abstract: Anthropogenic global warming and the depletion of nonrenewable resources necessitate a transition towards bioenergy to accelerate sustainable development and carbon neutrality. This study quantified the availability and energy potential of crop (cereals, legumes, roots and tubers) straws based on data from the Northern, North East and Savannah regions in Ghana. The annual technical straw potential was 2,967,933 tonnes, whilst the crop straws with the highest technical potential were yam (935,927 tonnes), groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…2 ) [ 31 ]. Previous studies [ 22 , 27 , 32 ] found that cassava stalk, yam stalk and maize cob should be prioritized for pellet production in Ghana. Mohammed et al [ 59 ] in their study did not prioritize all types of residues produced by maize (stalks, cobs, and husks) and rice (straw and husks).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 ) [ 31 ]. Previous studies [ 22 , 27 , 32 ] found that cassava stalk, yam stalk and maize cob should be prioritized for pellet production in Ghana. Mohammed et al [ 59 ] in their study did not prioritize all types of residues produced by maize (stalks, cobs, and husks) and rice (straw and husks).…”
Section: Resultsmentioning
confidence: 99%
“…Ghana can ensure constant pellet production by spreading out or localizing factories, as seen in Europe [ 201 ] and China [ 199 ]. Mid-South and Northern Ghana could be optimal sites for pellet processing facilities as copious amounts of crop residue, and wood waste are generated in these areas [ 27 , 31 ]. The Ghana Ministry of Transport and other stakeholders must tackle issues with poor road networks [ 217 ] and transport mediums to ameliorate transportation's associated inconveniences and dangers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual production for the period was 3,983,313, 3,849,396, and 4,074,085 in 2017, 2018, and 2019, respectively. Throughout this period, yam straws consistently had the highest production, while millet straws had the lowest 7 (Table 1). Wood residues from road construction, skidding trails, surface mining sites, and forest clearings for agriculture offer additional biomass sources.…”
Section: Introduction 1biomass Resources In Ghanamentioning
confidence: 99%
“…Amount of Typical Crop Residue Produced in Three Regions of Ghana (North, North East, and Savannah) from 2017 to 2019 in Tonnes7 …”
mentioning
confidence: 99%